Pro-resolving and anti-arthritic properties of the MC1 selective agonist PL8177 - Garrido-Mesa, Jose; Thomas, Bethan Lynne; Dodd, John; Spana, Carl; Perretti, Mauro; Montero-Melendez, Trinidad (Frontiers in Immunology, 2022)
Background: Melanocortins are peptides endowed with anti-inflammatory and pro-resolving activities. Many of these effects are mediated by the melanocortin receptor 1 (MC1) as reported in several experimental settings. As such, MC1 can be a viable target for the development of new therapies that mimic endogenous pro-resolving mediators. The aim of this study was to assess the immunopharmacology of a selective MC1 agonist (PL8177) in vitro and in a mouse model of inflammatory arthritis. Methods: PL8177 and the natural agonist αMSH were tested for activation of mouse and human melanocortin receptors (MC1,3,4,5), monitoring cAMP accumulation and ERK1/2 phosphorylation, using transiently transfected HEK293A cells. The anti-inflammatory and pro-resolving effects of PL8177 and αMSH were evaluated using mouse peritoneal macrophages. Finally, a model of K/BxN serum transfer induced arthritis was used to determine the in vivo potential of PL8177. Results: PL8177 activates mouse and human MC1 with apparent EC50 values of 0.01 and 1.49 nM, respectively, using the cAMP accumulation assay. Similar profiles were observed for the induction of ERK phosphorylation (EC50: 0.05 and 1.39 nM). PL8177 displays pro-resolving activity (enhanced macrophage efferocytosis) and counteracts the inflammatory profile of zymosan-stimulated macrophages, reducing the release of IL-1β, IL-6, TNF-α and CCL-2. In the context of joint inflammation, PL8177 (3mg/kg i.p.) reduces clinical score, paw swelling and incidence of severe disease as well as the recruitment of immune cells into the arthritic joint. Conclusion: These results demonstrate that the MC1 agonism with PL8177 affords therapeutic effects in inflammatory conditions including arthritis.